2004
DOI: 10.1046/j.1365-294x.2004.02076.x
|View full text |Cite
|
Sign up to set email alerts
|

New insights from fine‐scale spatial genetic structure analyses in plant populations

Abstract: Many empirical studies have assessed fine-scale spatial genetic structure (SGS), i.e. the nonrandom spatial distribution of genotypes, within plant populations using genetic markers and spatial autocorrelation techniques. These studies mostly provided qualitative descriptions of SGS, rendering quantitative comparisons among studies difficult. The theory of isolation by distance can predict the pattern of SGS under limited gene dispersal, suggesting new approaches, based on the relationship between pairwise rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

105
1,923
17
16

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,124 publications
(2,119 citation statements)
references
References 81 publications
105
1,923
17
16
Order By: Relevance
“…This is the most common pattern found in plants (Ashley 2010), and our observations are also consistent with the pattern frequently reported for insect‐pollinated species (Austerlitz et al. 2004; Smouse and Sork 2004; Vekemans and Hardy 2004). But in H. oldfieldii , most pollen movements were not to nearest neighbors but to plants >10 m away, including significant pollination from distant (>50 m away) sources.…”
Section: Discussionmentioning
confidence: 99%
“…This is the most common pattern found in plants (Ashley 2010), and our observations are also consistent with the pattern frequently reported for insect‐pollinated species (Austerlitz et al. 2004; Smouse and Sork 2004; Vekemans and Hardy 2004). But in H. oldfieldii , most pollen movements were not to nearest neighbors but to plants >10 m away, including significant pollination from distant (>50 m away) sources.…”
Section: Discussionmentioning
confidence: 99%
“…excluding the population from the island of Mallorca) and for each lineage and the hybrid zone separately. Regression was performed for the kinship coefficient between pairs of individuals (fij) (Loiselle et al, 1995) and their geographical distance (dij), to give a regression slope lnbd and its statistical significance (Vekemans & Hardy, 2004). Also, spatial autocorrelation methods were applied to examine spatial genetic structure (Smouse & Peakall, 1999).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Studies have shown that taxa with high dispersal capabilities maintain high levels of gene flow and express low levels of geographic structuring due to the homogenization of genetic diversity (Grant & Bowen, 1998; Beheregaray & Sunnucks, 2001; Manel, Schwartz, Luikart, & Taberlet, 2003; Gotoh, Chiba, Goto, Tamate, & Hanzawa, 2011; Manel & Holderegger, 2013). However, reduced dispersal capabilities minimize the amount of gene flow between populations, which may result in a nonrandom distribution of alleles (Templeton, Routman, & Phillips, 1995; Avise, 2000; Hanski, Erälahti, Kankare, Ovaskainen, & Sirén, 2004; Vekemans & Hardy, 2004). …”
Section: Introductionmentioning
confidence: 99%